The Students’ Ability in Translating a Narrative Text Using Dictionaries - Semiun, Thresia Trivict; Erna Tanesab; Edmundus Bouk (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
Translation is commonly done by the students when teaching and learning happens in the classroom. This study has two aims which are to find out the students’ ability in translating a narrative text using dictionaries and to reveal the students' difficulties in translating a narrative text using dictionaries. This study applied a descriptive qualitative research design. The instruments used to collect the data were a test and an interview. The subjects of the study were 28 students in the twelfth grade of SMA Nurul Falah Kefamenanu. The research result revealed that there were seven students (25%) who obtained an excellent level of mastery, and there were 19 students (68%) who obtained a good level of mastery. And then, there were two students (7% ) who obtained fair-level mastery. Meanwhile, no one of the students score less than 40, which indicated a poor level of mastery. Overall, the students’ ability in translating the narrative text could be categorized as good. The difficulties of the students in translating the text are as follows; first, the students did not have a dictionary, and they always use Google translate when they translate the text. Second, the students were lack of vocabulary. Last, the students were confused to translate the words and put them into good sentences.